Academic integrity in public administration programmes: Practical reflections on prevention and response. Issue 1 (March 2020) - Newman, Joshua
Academic integrity matters are relevant to all areas of university teaching, but they are of particular importance to degree programmes whose graduates intend to work in the public service. While a large body of scholarship exists on academic integrity, very little has been written that specifically relates to students who intend to pursue careers in the public sector. This article is a reflection of the author's experience as Academic Integrity Officer in the School of Social and Policy Studies at Flinders University in Adelaide, Australia, between January 2016 and July 2017, during which time 92 cases of suspected breaches of academic integrity were reviewed and adjudicated. An analysis of the cases presented here suggests that universities can make more use of preventative strategies than they currently do, and that more emphasis should be placed on prevention and less on punishment as a response.